(untitled) (Journal of Fatima Jinnah Medical University, 2018)
OBJECTIVE: To assess maternal outcome in patients with eclampsia in SGRH. MATERIAL AND METHOD: Descriptive study which was carried out in SGRH from January 2009 to December 2009. maternal outcome was measured in parameters of pulmonary oedema, renal failure, HELLP syndrome, cerebral haemorrhage and death.